Comparative transcriptome analyses of immune responses to LPS in peripheral blood mononuclear cells from the giant panda, human, mouse, and monkey - Li, Shun; Li, Caiwu; Chen, Lixiang; Yang, Hua; Ren, Xiaonan; Xu, Chunhua; Wu, Bin; Wang, Chao; Ling, Yun; Shen, Yinzhong; Lu, Hongzhou; Liu, Weiping; et al. (Frontiers in Genetics, 2023)
Gram-negative bacteria are major pathogens leading to illnesses in giant pandas. As the components of Gram-negative bacteria, Lipopolysaccharide (LPS) can activate immune responses in mammals (i.e. human, mice) through the recognition by Toll-like receptors (TLRs). However, how giant panda immune response to LPS stimulation and the differences between the giant panda with other mammals are still not fully known. In this study, we administrated the PBMCs (peripheral blood mononuclear cells) from giant panda, human, mouse, and monkey by LPS treatment at 6 hours and followed by RNA sequencing (RNA-seq) respectively, with the control of non-stimulation. KEGG analyses of differential expression genes (DEGs) pathways indicated that LPS could activate the classic signaling pathway of NF-kappa B in PBMCs from those four tested species. Thus, similar to the other three species, NF-κB is an LPS-responsive regulator of innate immune responses in giant panda. Furtherly, the expression patterns of adaptor genes, inflammatory cytokine genes, chemokines, interferon genes, cytokine genes related to cell growth and development, costimulatory molecules, Th1/Th2 cytokine genes, Th17 cytokine genes, Th9, and Th22 cytokine genes were compared among giant pandas and other three species. Our data indicated that besides the similar expression patterns of certain genes among giant pandas and other species, the unique expression pattern response to LPS in giant pandas was also discovered. In addition, Th9, Th17, and Th22 cells may be involved in the response to LPS in giant pandas at this tested time point. This study uncovers that LPS induced immune responses have different sensitivity and time line of response among giant panda with other mammals. This study facilitates further understanding of the role of TLR signaling pathway and the immune system in giant panda, which might be helpful for disease prevention and protection of giant panda.